2016
DOI: 10.1038/srep23364
|View full text |Cite
|
Sign up to set email alerts
|

Significant Broadband Photocurrent Enhancement by Au-CZTS Core-Shell Nanostructured Photocathodes

Abstract: Copper zinc tin sulfide (CZTS) is a promising material for harvesting solar energy due to its abundance and non-toxicity. However, its poor performance hinders their wide application. In this paper gold (Au) nanoparticles are successfully incorporated into CZTS to form Au@CZTS core-shell nanostructures. The photocathode of Au@CZTS nanostructures exhibits enhanced optical absorption characteristics and improved incident photon-to-current efficiency (IPCE) performance. It is demonstrated that using this photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…In another recent report by Zhang et al . where comparative study is being done on bare wurtzite CZTS and core@shell Au@wurtzite CZTS as CE material in DSSC shows that Au@CZTS shows better photoconversion efficiency that bare CZTS which is even 15.8% higher than Pt CE as shown in Figure a, b . The higher absorption of energy due to the plasmon resonance energy transfer (PRET) from localized surface plasmon resonance (LSPR) to embedded Au and lesser scattering at Au@CZTS interface are the contributing factor for above enhancement in photo conversion efficiency as shown in Figure c, d. CoPt tipping on CZTS nanoparticles in different composition (Co/Pt ratios: Co/Pt=0.5; Co/Pt=1; Co/Pt=2) have shown to improve the H 2 evolution efficiency in comparison to bare CZTS and even Au‐CZTS hybrid nanomaterial .…”
Section: Photoelectrochemical and Photocatalytic Applicationsmentioning
confidence: 96%
“…In another recent report by Zhang et al . where comparative study is being done on bare wurtzite CZTS and core@shell Au@wurtzite CZTS as CE material in DSSC shows that Au@CZTS shows better photoconversion efficiency that bare CZTS which is even 15.8% higher than Pt CE as shown in Figure a, b . The higher absorption of energy due to the plasmon resonance energy transfer (PRET) from localized surface plasmon resonance (LSPR) to embedded Au and lesser scattering at Au@CZTS interface are the contributing factor for above enhancement in photo conversion efficiency as shown in Figure c, d. CoPt tipping on CZTS nanoparticles in different composition (Co/Pt ratios: Co/Pt=0.5; Co/Pt=1; Co/Pt=2) have shown to improve the H 2 evolution efficiency in comparison to bare CZTS and even Au‐CZTS hybrid nanomaterial .…”
Section: Photoelectrochemical and Photocatalytic Applicationsmentioning
confidence: 96%
“…135 Plasmonic Au Nanoparticle core is actually helps to CZTS nanocrystalline shell in a core-shell mechanism manner to develop Au@CZTS coreshell nanostructures which actually enhance the efficiency of the device as reported by . 136 Expect disk, plates and particles nanorods can be also prepared by a facile solvothermal method as reported by Miyauchi et al (2012). 137 Interestingly, CZTS in form of nanofibers has also been prepared by Mali et al (2014) by electrospinning process using the polyvinylpyrrolidone (PVP) and cellulose acetate solvent separately.…”
Section: Synthesis and Morphology Evaluation Of Cu 2 Snznsmentioning
confidence: 98%
“…Among the available Pt-free electrocatalyst materials, transition metal oxides, sulphides, nitrides and carbides showed promising electrocatalytic performance in DSSCs. [10][11][12][13][14] In addition, the quaternary semiconductor CZTS geared notable attention in DSSCs owing to less toxic, earth abundance, [15][16][17][18] and high hole concentration [19] of ~1.2×10 15 to 3.1×10 20 cm -3 . Digraskar et al [20] demonstrated the feasibility of CZTS electrocatalyst in powder form toward water reduction into hydrogen fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The CZTS films can be directly formed on substrates or deposited from the presynthesised nanocrystals. The pre-synthesised colloidal CZTS nanocrystals or inks were transformed onto conducting substrates by spin coating, [15,16] or spray coating [17]. The hydrothermal/solvothermaldeposition, [18,24]electrospun, [25,26] spray coating, [27] electrodeposition, [28,29] sputtering, [23] and pulsed laser deposition [24] methods have been used for direct deposition of CZTS onto substrates.…”
Section: Introductionmentioning
confidence: 99%